No resilience without partners: A case study on German small and medium-sized enterprises in the context of COVID-19 - Anna Trunk; Hendrik Birkel (Schmalenbach Journal of Business Research (SBUR), 2022)
Much research has been conducted on the effects of COVID-19 on company and supply chain resilience. However, few contributions have focused on small and medium-sized enterprises. These companies are claimed to be the drivers of economic growth but often lack access to resources and alternatives when interruptions occur, making them a bottleneck for supply chains. Using a multiple case study approach, this paper links resilience theory to the design of the relationships between eight German small and medium-sized enterprises and their suppliers and customers. It analyzes the way in which these companies combine contractual and relational investments across their supply chain flows of product, finance, and information in order to improve resilience. Company representatives were interviewed on three occasions between June 2018 and December 2020, that is, before COVID-19 and during the lockdowns. The results of the case study explain why and how companies of this type have been able to anticipate and manage the crisis. The interviews revealed that those companies that made the largest investments in the relational aspects of their partnerships while safeguarding product and financial flows through contracts performed best. In principle, contractual investments are higher in partnerships with suppliers. However, the precise combination of contractual and relational investments depends on the business model, the business philosophy of the CEO, and the allocation of power within the supply chain. These findings indicate that, when collaborating with small businesses, supply chain partners should focus on building relationships in order to create resilience in the supply chain.
Keywords: D23; D8; H12; L14; L22; M19; M39; 650; Supply chain management (SCM); Small and medium-sized enterprises (SME); COVID-19; Case study; Resilience